(3cTa GdMbGFbs - (3CMeO Hf jhSa Hf GdMSf Hf QGaY GHf GdMSjf Hf ShjOGf GdTjHGfqj GdehUdj, ehab GdOjf CHh GdYHGS GdchGTj , J (B680 (3g`s ((3EHQGgje Hf eMeO GdTgjQ HGdeLGhQ s)
(3ChdgG (B:s
(3ShQI GdYfcHhJ ecjI Ch eOfjI Ch Edi YTQ efgG eci hHGbjgG eOfi Ch HGdYcS s
(3BNQgG (B:s
(3hgPG BNQ GdJaSjQ hGdMeO ddg Ydi GdJjSjQq s
(3GdfSNI HgG MhGTs
(3GdfSNI efbhdI ef NW GdeDda hgj fSNI NRGFfjIs
(3cJHJ HYV GdcdeGJ GdbdjdI HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs